2010
DOI: 10.1007/s12011-010-8793-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forced Running Exercise on Cognitive Function and Its Relation to Zinc Homeostasis-Related Gene Expression in Rat Hippocampus

Abstract: Voluntary exercise has been implicated to be beneficial for overall health and cognitive function in both clinical and experimental studies, but little is presently known about forced physical exercise on cognition and underlying molecular mechanism. We have used real-time RT-PCR to analyze gene expression in hippocampus, in the presence and absence of physical exercise, during spatial learning of rats in the Morris water maze. Our results show distinct zinc homeostasis-related gene expression profiles associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…investigated the effects of different zinc concentrations in the diet on long-term neurobehavioral and seizure thresholds following lithium chloride/pilocarpine-induced developmental seizures. They found that zinc supplementation for 4 weeks significantly improved injury-related changes, and rescued abnormalities in GPR39, ZnT-3, and MBP expression in the hippocampus, which suggests that the role of zinc ions in developmental convulsive brain injury may not be purely excitotoxic as previously thought ( 7 9 ), but may play a protective role in the brain as mentioned earlier ( 10 ). In a perspective article by Doenyas , a more comprehensive approach termed the “gut-immune-endocrine-brain” axis, is taken, based on which a personalized treatment plan for autism spectrum disorder (ASD) is presented.…”
Section: Introductionsupporting
confidence: 54%
“…investigated the effects of different zinc concentrations in the diet on long-term neurobehavioral and seizure thresholds following lithium chloride/pilocarpine-induced developmental seizures. They found that zinc supplementation for 4 weeks significantly improved injury-related changes, and rescued abnormalities in GPR39, ZnT-3, and MBP expression in the hippocampus, which suggests that the role of zinc ions in developmental convulsive brain injury may not be purely excitotoxic as previously thought ( 7 9 ), but may play a protective role in the brain as mentioned earlier ( 10 ). In a perspective article by Doenyas , a more comprehensive approach termed the “gut-immune-endocrine-brain” axis, is taken, based on which a personalized treatment plan for autism spectrum disorder (ASD) is presented.…”
Section: Introductionsupporting
confidence: 54%
“…Forced physical exercise improves cognitive ability and mobilizes mRNA expression of zinc transporters (ZnT-2, ZnT-4, ZnT-5, ZnT-6, ZnT-7), metallothioneins, divalent cation transporter-1 and Zrt-Irt like proteins-7 [34]. …”
Section: Discussionmentioning
confidence: 99%
“…The human seizures frequently occur early in life. Zn 2+ is one of the most abundant divalent metal ions in the CNS (Chimienti et al, 2003; Devirgiliis et al, 2007), and zinc transporters show dynamic expression pattern in animal seizure model (Ni et al, 2010, 2011a, b). Zinc transporters ZnT3, ZnT4, and ZIP7 are upregulated in cultured HT22 cells and flurothyl-induced recurrent neonatal seizures, and these altered expressions were reversed by leptin treatment (Jin et al, 2018; Li et al, 2018).…”
Section: Neuroprotective Roles Of Leptinmentioning
confidence: 99%